The potential application of natural products in cutaneous wound healing: A review of preclinical evidence - Liu, E; Gao, Hongjin; Zhao, YiJia; Pang, Yaobing; Yao, Yejing; Yang, Zhengru; Zhang, Xueer; Wang, YanJin; Yang, Siming; Ma, Xiao; Zeng, Jinhao; Guo, Jing (Frontiers in Pharmacology, 2022)
Under normal circumstances, wound healing can be summarized as three processes. These include inflammation, proliferation, and remodeling. The vast majority of wounds heal rapidly; however, a large percentage of nonhealing wounds have still not been studied significantly. The factors affecting wound nonhealing are complex and diverse, and identifying an effective solution from nature becomes a key goal of research. This study aimed to highlight and review the mechanisms and targets of natural products (NPs) for treating nonhealing wounds. The results of relevant studies have shown that the effects of NPs are associated with PI3K-AKT, P38MAPK, fibroblast growth factor, MAPK, and ERK signaling pathways and involve tumor growth factor (TNF), vascular endothelial growth factor, TNF-α, interleukin-1β, and expression of other cytokines and proteins. The 25 NPs that contribute to wound healing were systematically summarized by an inductive collation of the six major classes of compounds, including saponins, polyphenols, flavonoids, anthraquinones, polysaccharides, and others, which will further direct the attention to the active components of NPs and provide research ideas for further development of new products for wound healing.